GAMBARAN MOTIVASI MAHASISWA BIMBINGAN DAN KONSELING UNIVERSITAS PGRI PALEMBANG DALAM MENGIKUTI PERKULIAHAN - Sari, Kurnia (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Lecturing activities ideally that there is a good interaction between teachers and lecturers. But there are still things that become polemic in the lecture is the existence of students who have no motivation to follow the ongoing lectures with various causes. The purpose of this study is to determine the description of student motivation in following the lecture. This research is quantitative descriptive. The research population is all students of 3rd semester at Universitas PGRI Palembang 2016/2017 academic year as many as 68 people. The sample size is 58 people using Slovin formula. The instrument used is a closed questionnaire using Likert scale model. Data analysis techniques using the formula percentage. The findings of this study indicate that the motivation of students guidance and counseling PGRI Palembang universities included in the category of being. This is seen on the average score of 78.4, with a frequency of 24 or can be in percentage with a value of 41.4%. By knowing the description of motivation, it is expected to help lecturers to improve the quality of teaching by applying various teaching methods, as well as for students to improve themselves by increasing the motivation in following the lecture by following the guidance and counseling services both in classical, group and individual in Guidance and Counseling Unit. Keywords─ Student motivation in following lectures